Early childhood development and stunting: Findings from the MAL‐ED birth cohort study in Bangladesh. Issue 1 (6th August 2019) - Nahar, Baitun; Hossain, Muttaquina; Mahfuz, Mustafa; Islam, M. Munirul; Hossain, Md Iqbal; Murray‐Kolb, Laura E.; Seidman, Jessica C.; Ahmed, Tahmeed
Abstract: Information on the association between stunting and child development is limited from low‐income settings including Bangladesh where 36% of children under‐ 5 are stunted. This study aimed to explore differences in early childhood development (ECD) between stunted (length‐for‐age z ‐score [LAZ] < −2) and nonstunted (LAZ ≥ −2) children in Bangladesh. Children ( n  = 265) aged 6–24 months who participated in the MAL‐ED birth cohort study were evaluated by trained psychologists at 6, 15, and 24 months of age using the Bayley Scales of Infant and Toddler Development‐III; child length and weight were measured using standard procedures. ECD scores ( z ‐scores derived from cognitive, motor, language and socio‐emotional skills) were compared between stunted, underweight (weight‐for‐age z ‐score < −2), and wasted (weight‐for‐length z ‐score < −2) children, controlling for child age and sex and maternal age, education, body mass index (BMI), and depressive symptoms. Stunted children had significantly lower ECD scores than their nonstunted peers on cognitive ( P  = .049), motor ( P  < .001), language ( P  < .001) and social–emotional ( P  = .038) scales where boys had significantly lower fine motor skills compared with girls ( P  = .027). Mother's schooling and BMI were significant predictors of ECD. Similar to stunting, underweight children had developmental deficits in all domains (cognitive: P  = .001; fine motor: P  = .039, and P  < .001 for both gross motor and total motor; expressive communication: P  = .032; total language: P  = .013; social–emotional development: P  = .017). Wasted children had poor motor skills ( P  = .006 for the fine motor; P  < .001 for both gross motor and total motor development) compared with the nonwasted peers. Early childhood stunting and underweight were associated with poor developmental outcomes in Bangladesh.